(untitled) (Journal of Economic Research & Business Administration, 2022)
The role of equipping each railway station with modern automatic and telemechanical devices is invaluable. However, there is an opinion that equipping the station with electric centralization requires huge investments and the payback period is ten years. In the course of the research, the reasons for the long-term payback of the introduction of electric centralization at the station were determined. It is revealed that according to the existing methodology for assessing the economic prospects for the introduction of a new technology of electric centralization, the number of shunting locomotives saved is not taken into account due to the acceleration of the duration of technological operations at the station. This article discusses a new methodology for assessing the economic efficiency of the introduction of an electric centralization system on the example of the development of the infrastructure of the station «Z». The procedure for determining the initial capital investments in the development of the station infrastructure and equipping it with an electric centralization system is presented. The payback period of investments, the rate of return and the annual cost savings spent within the framework of the implemented electric centralization system are shown. Key words: railway infrastructure, electrical centralization, fuels, economic efficiency, net present value, rate of return, capital investment.